Mobile solutions in road transport - Batarlienė, Nijolė; Baublys, Adolfas (Transport, 2007)
The article dwells on the aspects of mobile solutions of public information and transport. The work presents major decision making principles based on object positioning and a system of positioning‐based GSM solutions. The newly developed remote identification systems for transport facilities and goods and passenger transport and their schematic view are presented. The main units of the remote identification system of vehicles and goods embrace: TI portal, TVIM portal, content control system (SMS, GPRS), mobile phone, the unit for stating the geographical position of vehicles and goods. Portals are designed so that the data provided by various systems of observation, such as GSM, GPS, WLAN, wireless internet, etc., can be used there. Portals (TI and TVIM) can also be used for testing, complex evaluation of monitoring functions as well as for providing the data on geographical location of objects, transmitting data to mobile telephones, etc. Purposes and functions of the portals are presented. The article describes the facility of implementing the mobile user concept, changes made in the portal pages to support the mobile users. First Published Online: 27 Oct 2010